Muqāranah Dalāliyyah bayna al- ‘Aqlwa al-Qalb wa al-Nafswa al-Rūhfī al-Qur’ān al-Karīm: Semantic Study Analysis - Kamil, Muhammad Fauzan; Tatang; Tantowi, Yusuf Ali (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study examines the relationship between the meanings of the terms ‘aql, qalb, nafs, and rūḥ in the Qur’an, which are often understood separately or equated. The main problem is the tendency for partial readings that simplify the functions of these four terms. This study aims to systematically explain the differences in function and the relationships between the meanings of these four terms. The method used is a qualitative literature study based on the semantic approach of the Qur’an to the verses of the Qur’an containing these four terms, which are analyzed through determining the basic meaning, syntagmatic and paradigmatic relationships, and triangulation with previous interpretations and studies. The results show that ‘aql functions as the activity of thinking and understanding, qalb as the center of moral awareness and acceptance of truth, nafs as the subject of moral responsibility, and rūḥ as the principle of life derived from God’s commands. These four terms form an interrelated system of meaning and are not synonymous. It can be concluded that a relational understanding of these terms contributes to the study of the meaning of the Qur’an and has pedagogical implications in learning that emphasizes conceptual and contextual understanding, not just literal translation.